31P NMR characterization of terminal phosphates induced on DNA by the artificial nuclease 'Mn-TMPyP/KHSO5' in comparison with DNases I and II. - Gasmi, G (1991)
Phosphorus-31 NMR has been applied to the characterization of terminal phosphates on fragments of calf thymus DNA induced by three different nuclease systems: DNase I, DNase II and the artificial nuclease 'Mn-TMPyP/KHSO5'. In this last case, the oxidative damage to deoxyribose leads to two monophosphates esters (at the 3' and 5' ends) on both sides of the cleavage site. This method constitutes a promising approach to visualise the phosphate termini generated in DNA or RNA cleavage by cytotoxic drugs or chemical nucleases and provides a novel insight into the molecular aspects of their mechanism of action.